The Faithful Friend - San Souci, Robert D.; Pinkney, J. Brian (New York, 1995)
A retelling of the traditional tale from the French West Indies in which two friends, Clement and Hippolyte, encounter love, zombies, and danger on the island of Martinique.
Accelerated Reader AR